The An Analysis of Student’s Error in using Personal Pronoun on Writing Descriptive Text - Sultoni Hakidi; Suparmi Suparmi; Rahma Dania (Universitas Putra Indonesia YPTK Padang, 2021)
The research was aimed to analyse the errors made by students in using personal pronoun on writing descriptive text of tenth grade SMKN 9 Padang in the academic year of 2021/2022. The subject of this research consist of 15 students in X TB 5. The objectives of the study were (1) To find the types of error made by students in using personal pronoun on writing descriptive text. (2) To find out the couses of errors made by students in using personal pronoun on writing descriptive text.This research used qualitative approach with descriptive approach. The errors Were collected, identified, and classified based on the surface structure Taxonomy by Dulay. It was specified by four types of errors namely omission, addition, misordering, and misformation.The result showed (1) the most common errors made by students were misformation (48.84%). The second was error in addition with frequency (27.91%). The third error was omission (20.93%). The lowest frequency of error was misordering (2.31%). (2) The research proved that the students still did not understand the material given by teacher. The errors occurred because the students were mostly confused about the material given and they did not study well. Abstract The research was aimed to analyse the errors made by students in using personal pronoun on writing descriptive text of tenth grade SMKN 9 Padang in the academic year of 2021/2022. The subject of this research consist of 15 students in X TB 5. The objectives of the study were (1) To find the types of error made by students in using personal pronoun on writing descriptive text. (2) To find out the couses of errors made by students in using personal pronoun on writing descriptive text.This research used qualitative approach with descriptive approach. The errors Were collected, identified, and classified based on the surface structure Taxonomy by Dulay. It was specified by four types of errors namely omission, addition, misordering, and misformation.The result showed (1) the most common errors made by students were misformation (48.84%). The second was error in addition with frequency (27.91%). The third error was omission (20.93%). The lowest frequency of error was misordering (2.31%). (2) The research proved that the students still did not understand the material given by teacher. The errors occurred because the students were mostly confused about the material given and they did not study well. Key Word : Error analysis; Personal Pronoun; Descriptive Writing Text. Key Word : Error analysis; Personal Pronoun; Descriptive Writing Text.